Studi Perbandingan Model Pembelajaran Kooperatif Tipe Jigsaw dan NHT (Numbered Head Together)Terhadap Hasil Belajar Stoikiometri Siswa Kelas X SMAN 8 Palu - Nizar Nizar; Irwan Said; Suherman Suherman (Jurnal Akademika Kimia, 2016)
The aim of this study is to compare the learning outcomes of student in SMA Negeri 8 Palu using the cooperative learning model between jigsaw and NHT (numbered head together) on the stoichiometry. This research using a quasi-experimental design with factorial 2 x 2. The population of this study is all student of class X SMA 8 Palu with academic year 2015/2016 which consists of four classes. The sample of this study consists of two classes, namely class XB with amount of 16 students (experimental class) and class XC with amount of 17 students (control class) which was determined by purposive sampling. Data was collected by using test instruments, namely an achievement test that contains the stoichiometry material. The examination of data was conducted by using statistical analysis t-test two sides and one side (right side) non-parametric or Mann-Whitney U test. The average score of the learning outcomes of student by using the jigsaw type was (78.00; SD = 13.63), and by using NHT type was (70.47; SD = 16.51). Based on statistical analysis of the hypothesis test for two sides, it was obtained a value of 0.195 Asymp sig (2-tailed) and was obtained a value 0.204 Exact Sig (1-tailed) of 0.204, both of datas were at the rejection area of H0 which was a significance value greater than 0.05 (P> 0.05). Therefore, it can be concluded that there was a difference in learning outcomes using the cooperative model jigsaw type with NHT type, furthermore the type of jigsaw better than the NHT on the learning outcomes of students of stoichiometry in class X SMA Negeri 8 Palu.